2018
DOI: 10.1111/ced.13678
|View full text |Cite
|
Sign up to set email alerts
|

Utility of tissue elafin as an immunohistochemical marker for diagnosis of acute skin graft-versus-host disease: a pilot study

Abstract: Tissue elafin is a useful immunohistochemical marker for acute skin GvHD. However, larger studies are needed to validate these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
0
16
1
Order By: Relevance
“…They also demonstrated that elafin-high aGVHD lesions presented with epidermal thickening and were associated with poor clinical outcomes [12]. More recently, Mahabal GD et al indicated that tissue elafin is a useful immunohistochemical marker for skin aGVHD, and the sensitivity and specificity of elafin immunohistochemistry to predict acute skin GVHD were 100 and 75%, respectively [67]. Although the biomarker of skin aGVHD, elafin, is more specific, most skin aGVHD is easy to control, and the incidence of associated mortality is very low.…”
Section: Exploratory Studies Of Agvhd Biomarkersmentioning
confidence: 99%
“…They also demonstrated that elafin-high aGVHD lesions presented with epidermal thickening and were associated with poor clinical outcomes [12]. More recently, Mahabal GD et al indicated that tissue elafin is a useful immunohistochemical marker for skin aGVHD, and the sensitivity and specificity of elafin immunohistochemistry to predict acute skin GVHD were 100 and 75%, respectively [67]. Although the biomarker of skin aGVHD, elafin, is more specific, most skin aGVHD is easy to control, and the incidence of associated mortality is very low.…”
Section: Exploratory Studies Of Agvhd Biomarkersmentioning
confidence: 99%
“…Several authors have attempted to identify histopathological and IHC markers that allow the distinction of aGVHD from SDRs . In the present study, vacuolar interface changes were observed in all aGVHD and all SDRs cases.…”
Section: Discussionmentioning
confidence: 50%
“…In our study, we found infiltrates by CD4+ and CD8+ T lymphocytes in both aGVDH and SDRs, with no significant differences between them. The increased expression of elafin, intercellular adhesion molecule‐I (ICAM‐1), and HLA‐DR antigens in keratinocytes have further been reported in aGVHD skin biopsies …”
Section: Discussionmentioning
confidence: 82%
“…[24] Skin biomarkers Elafin Diagnostic Elafin expression in the skin was associated with cutaneous aGVHD diagnosis. [38] Skin and intestinal biomarkers…”
Section: Reg3amentioning
confidence: 99%